DNA under confinement and the use of DNA as confinement - Brutzer, Hergen; Sperling, Evgeni; Günther, Katrin; Dikic, Jasmina; Schwarz, Friedrich; Klaue, Daniel; Cichos, Frank; Mertig, Michael; Seidel, Ralf (Diffusion Fundamentals, 2015)
In living systems DNA is subjected to considerable confinement but the molecule acts itself also as a confinement mechanism for cellular structures. Here we present investigations that study DNA under the confinement of supercoiling and within nanofluidic channels. Furthermore, we use DNA to confine the motion of microscopic and nanoscopic objects. In particular, we show how the motion dynamics of DNA-attached magnetic particles under external tension is affected and how DNA can confine the diffusion of enzymes to one dimension to follow the DNA contour.